Analisis Exergoeconomic Pembangkit Listrik Tenaga Uap (PLTU) Dual Fuel Line 2 PT Riau Andalan Pulp And Paper (RAPP) 100 MW Pangkalan Kerinci - Binsar Martua Parulian Manurung; Romy Romy; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The dual fuel line 2 100MW steam power plant (PLTU) is one of the power plants owned by PT Riau Andalan Pulp and Paper. To produce steam PLTU line 2, PT RAPP used biomass as the main fuel and natural gas as an alternative fuel to achieve the required steam production target. The combination of exergy analysis (second law of thermodinamics) with economic analysis is exergoeconomic. With this exergoeconomic analysis the value of losses in each component of the steam power plant is more noticeable because it is already in the value of the currency. By carrying out this research the value of the cost of loss can be identified specifically, from the highest loss to the lowest loss. At the dual fuel line 2 PT RAPP 100MW steam power plant the biggest cost of the loss was at the boiler at US 533.048,48/hour, followed by the HP pre-heater 2 for US 262.869,97/hour, the HP pre-heater 1 for US 83.153,52/hour, condenser US44.063,03/hour, pump 2 US42.846,85/hour, feedwater tank US34.849,08/hour, steam turbine US234.05/hour and the smallest was pump 1 US71,48/hour. With a total value of a loss of US 1.011.509,52/hour. Through this research, it was expected that the value of the cost of losses due to exergy destruction can be reduced. Keyword: Pembangkit Listrik Tenaga Uap, Exergy, Exergoeconomic